Myasthenic crisis demanding mechanical ventilation: A multicenter analysis of 250 cases. (21st January 2020) - Neumann, Bernhard; Angstwurm, Klemens; Mergenthaler, Philipp; Kohler, Siegfried; Schönenberger, Silvia; Bösel, Julian; Neumann, Ursula; Vidal, Amelie; Huttner, Hagen B.; Gerner, Stefan T.; Thieme, Andrea; Steinbrecher, Andreas; et al.
Abstract : Objective: To determine demographic characteristics, clinical features, treatment regimens, and outcome of myasthenic crisis (MC) requiring mechanical ventilation (MV). Methods: Analysis of patients who presented with MC between 2006 and 2015 in a German multicenter retrospective study. Results: We identified 250 cases in 12 participating centers. Median age at crisis was 72 years. Median duration of MV was 12 days. Prolonged ventilation (>15 days) depended on age ( p = 0.0001), late-onset myasthenia gravis (MG), a high Myasthenia Gravis Foundation of America Class before crisis ( p = 0.0001 for IVb, odds ratio [OR] = infinite), number of comorbidities (>3 comorbidities: p = 0.002, OR 2.99), pneumonia ( p = 0.0001, OR 3.13), and resuscitation ( p = 0.0008, OR 9.15). MV at discharge from hospital was necessary in 20.5% of survivors. Patients with early-onset MG ( p = 0.0001, OR 0.21), thymus hyperplasia ( p = 0.002, OR 0), and successful noninvasive ventilation trial were more likely to be ventilated for less than 15 days. Noninvasive ventilation in 92 cases was sufficient in 38%, which was accompanied by a significantly shorter duration of ventilation ( p = 0.001) and intensive care unit (ICU) stay ( p = 0.01). IV immunoglobulins, plasma exchange, and immunoadsorption were more likely to be combined sequentially if the duration of MV and the stay in an ICU extended ( p = 0.0503, OR 2.05). Patients who received plasma exchange or immunoadsorption as first-line therapy needed invasive ventilation significantly less often ( p = 0.003). In-hospital mortality was 12%, which was significantly associated with the number of comorbidities (>3) and complications such as acute respiratory distress syndrome and resuscitation. Main cause of death was multiorgan failure, mostly due to sepsis. Conclusion: Mortality and duration of MC remained comparable to previous reports despite higher age and a high disease burden in our study. Prevention and treatment of complications and specialized neurointensive care are the cornerstones in order to improve outcome.